2013
DOI: 10.7314/apjcp.2013.14.1.121
|View full text |Cite
|
Sign up to set email alerts
|

Significance of HPV Infection and Genic Mutation of APC and K-ras in Patients with Rectal Cancer

Abstract: Background: Significance of HPV infection and genic mutation of APC and K-ras in rectal cancer has been investigated but not clarified. The objective of our study was to investigate these parameters in patients with rectal cancer to analyze correlations with biological behaviour, to determine relationships among the three, and also to demonstrate survival prognosis effects. Methods: From December 2007 to September 2008, 75 rectal cancer cases confirmed by histopathology in the Tumor Hospital of Xinjiang Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The positivity ratio of HPV detection in CRC samples was varied population wise from 0% [ 11 , 12 , 17 , 23 , 26 , 32 , 41 , 43 , 45 , 46 , 50 , 59 ] to 100% [ 13 , 54 ] in all the 59 studies, whereas the positivity ratio of HPV detection in normal and adjacent/benign samples was varied from 0% [ 21 , 22 , 29 , 30 , 43 , 49 ] to 84% (28) and 0% [ 17 , 22 , 26 , 41 , 42 , 45 , 46 , 50 , 52 , 57 ] to 69.56% [ 54 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The positivity ratio of HPV detection in CRC samples was varied population wise from 0% [ 11 , 12 , 17 , 23 , 26 , 32 , 41 , 43 , 45 , 46 , 50 , 59 ] to 100% [ 13 , 54 ] in all the 59 studies, whereas the positivity ratio of HPV detection in normal and adjacent/benign samples was varied from 0% [ 21 , 22 , 29 , 30 , 43 , 49 ] to 84% (28) and 0% [ 17 , 22 , 26 , 41 , 42 , 45 , 46 , 50 , 52 , 57 ] to 69.56% [ 54 ], respectively.…”
Section: Resultsmentioning
confidence: 99%
“…reported HPV infection only in rectal cancer together with the highest HPV infection rate (71%) in all studies [22]. With respect to the site of cancer, a higher pooled OR was founded in rectal cancer.…”
Section: Subgroup Analysismentioning
confidence: 88%
“…Twelve papers that contained no relevant information were also excluded. Ten papers were included in the final meta-analysis [20][21][22][23][24][25][26][27][28][29].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The increase in surgical difficulty as a result of obesity may decrease the rate of sphincter preservation in patients from the Uygur ethnicity (36,37). Furthermore, on an economical and cognitive level, rectal cancer in Uygur populations is generally diagnosed much later in the disease stage, resulting in a larger tumor size and deeper invasion, which greatly influences the rate of sphincter preservation (38)(39)(40). In the present study, univariate analysis demonstrated that the sphincter-preserving factor was significantly associated with gender, BMI, age and tumor grade.…”
Section: Discussionmentioning
confidence: 99%